Pengaruh Karang Taruna Dalam Membentuk Karakter Positif Dan Etika Sosial Pemuda Di Desa Balonggabus - Chintia Sari; Wahyu Eko Pujianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research uses a literature review approach to investigate the role of Karang Taruna in preserving local culture and values ​​in Balonggabus Village. Through analysis of the latest findings, this research examines how Karang Taruna collaborates with the government and society to maintain cultural identity in the era of globalization. Literature findings illustrate joint efforts in preserving traditions, encouraging local entrepreneurship, and creating a balance between modernity and local values. The results of this research provide in-depth insight into the contribution of Karang Taruna as an agent for preserving cultural heritage, as well as how this collaboration creates a village that is dynamic and open to developments over time. This study provides a theoretical basis for understanding the role of Karang Taruna in facing the challenges of globalization while maintaining local wisdom.